(untitled) (Eurasian Journal of Humanities and Social Sciences, 2025)
This article shows that the concepts of "communication", "activity" are closely related to such a category as "relationship" (Andreeva G. M., 1980; Boda-Lev A. A., 1994; Levchenko E. V., 2003; Leontiev A. A., 1975) [4, 21, 106, 108], on the one hand, the formation and development of relationships occur in the interaction of a person with other people, on the other hand, the relationship itself has a significant impact on the communication process, and although relationships are closely related to communication and activity, they are not limited to communication and joint activities, but represent a "special type of social environment" [167, p. 5]. The theoretical foundations of the concepts of the theoretical foundations of the speech relations of parents with children with autism syndrome are widely covered